EKSISTENSI BUDAYA PATRON KLIEN DALAM PESANTREN: Studi Hubungan Antara Kyai dan Santri - Setiawan, Eko (ULUL ALBAB Jurnal Studi Islam, 2012)
Â This study aims to determine how the image of social interaction patterns kyai and santri, to know the form of the changing patterns of social interaction that occurs between the kyai and santri after the modernization in the period 2005-2012, to determine what factors are causing cultural patron clients are able to survive until now. This is a qualitative research which uses a case study model. This study seeks to understand the cultural significance of patron-client relationships kyai and santri. To understand the meaning of relationships between kyai and santri, this study uses theoretical orientation or theoretical perspective with a phenomenological approach. The location of this research is in Pondok Pesantren Daarul Fikri Mulyoagung Dau Malang. Pondok Pesantren Daarul Fikri is an independent institution not affiliated to any organization or group. This makes Pondok Pesantren Daarul Fikri as educational institutions that promotes educational ideals of purity and free from political interests or certain groups.Â Â